Blood pressure, glycemic control, and white matter hyperintensity progression in type 2 diabetics. (12th March 2019) - de Havenon, Adam; Majersik, Jennifer J.; Tirschwell, David L.; McNally, J. Scott; Stoddard, Gregory; Rost, Natalia S.
Abstract : Objective: To determine whether higher blood pressure mean (BPM) or hemoglobin A1c is associated with progression of white matter hyperintensity (WMH) on MRI in patients with type 2 diabetes, and whether intensive blood pressure or glycemic control can reduce that progression. Methods: We performed a secondary analysis of the Action to Control Cardiovascular Risk in Diabetes Memory in Diabetes (ACCORD MIND) research materials. The primary outcome is change in WMH volume (ΔWMH) between a baseline and month-40 MRI, and the primary predictor is BPM and A1c between the MRIs. Additional analyses compared ΔWMH in the intensive vs standard glycemic control randomization arms (n = 502) and intensive vs standard blood pressure control randomization arms (n = 314). Results: Higher systolic BPM, but not diastolic BPM or A1c, was associated with WMH progression. The ΔWMH in tertiles of increasing systolic BPM (115 ± 4, 127 ± 3, and 139 ± 6 mm Hg) was 0.7, 0.9, and 1.2 cm 3 ( p < 0.001). ΔWMH was lower in the intensive vs standard blood pressure control randomization arm (ΔWMH = 0.67 ± 0.95 vs 1.16 ± 1.13 cm 3, p < 0.001), but there was no difference in the glycemic control arms ( p = 0.917). Conclusion: In ACCORD MIND, higher systolic blood pressure was associated with WMH progression. The intensive blood pressure control intervention reduced this progression. Comorbid diabetes and hypertension has synergistic deleterious properties that increase the risk of micro- and macrovascular complications. These results provide further support for an aggressive approach to blood pressure control in type 2 diabetics.